2017
DOI: 10.1002/app.45425
|View full text |Cite
|
Sign up to set email alerts
|

Quasi‐isothermal DSC testing of epoxy adhesives using initial fast heating rates

Abstract: Three major factors decrease the accuracy of the cure measurement in standard-isothermal testing using differential scanning calorimetry (DSC). First, cure occurs during the heating step. Second, data are lost during the stabilization period between the dynamic and isothermal step. Third, the baseline selection requires a modification to the protocol. An alternative, which is explored in this study, is the use of fast ramps, which decrease the heating time, but this has been avoided due to overshoot that occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Epoxy resins are one of the most important classes of thermosetting materials that have attracted considerable attention due to their outstanding mechanical, electrical, chemical, and thermal properties. Epoxy resins are used in various engineering applications such as structural adhesives, coatings, composite materials, microelectronic encapsulants, and as skin binding in surgical incisions . Epoxies display a high degree of crosslinking as thermosetting materials, which provide them with useful properties.…”
Section: Introductionmentioning
confidence: 99%
“…Epoxy resins are one of the most important classes of thermosetting materials that have attracted considerable attention due to their outstanding mechanical, electrical, chemical, and thermal properties. Epoxy resins are used in various engineering applications such as structural adhesives, coatings, composite materials, microelectronic encapsulants, and as skin binding in surgical incisions . Epoxies display a high degree of crosslinking as thermosetting materials, which provide them with useful properties.…”
Section: Introductionmentioning
confidence: 99%
“…The same equation was valid to model the data with initial slow and fast ramp. The reader is encouraged to review a complete analysis of the fast ramp method reported in another article …”
Section: Resultsmentioning
confidence: 99%
“…33 Isothermal DSC scans may be impaired by problems in defining a correct base line, which led to specific test methods containing a comprehensive combination of dynamical and isothermal tests. 37,38 The determination of partial DOC and T g by DSC scans is more flexible than mechanical tests like DMA as less effort for sample preparation is required. Furthermore, the DSC signal is more sensitive to minor changes of the thermodynamic properties like aging effects.…”
Section: Reaction Kinetic Model and Phase Transitionsmentioning
confidence: 99%